2022
DOI: 10.1016/j.psj.2021.101535
|View full text |Cite
|
Sign up to set email alerts
|

Starving for nutrients: anorexia during infection with parasites in broilers is affected by diet composition

Abstract: In 2 experiments, we investigated whether diet composition plays a role in pathogen-induced anorexia, the voluntary reduction in ADFI during infection in broilers. We hypothesized that either energy or CP dietary content could influence the extent of anorexia in Ross 308 broilers and infection outcomes with Eimeria maxima . From d 13 of age, half of the birds were infected, and half were uninfected. ADFI was measured daily, and BW every 3 d until d 29. Oocyst excretion was measured daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…It has been reported that the mTOR pathway is more sensitive to BCAA in the skeletal muscle ( Yoshizawa et al, 2013 ) where the majority of its uptake occurs ( Holeček, 2018 ). Consequently, BCAA supplementation could primarily benefit the skeletal muscle for protein synthesis rather than intestinal epithelial cells and immune cells, especially during Eimeria infection, where nutrient availability is reduced due to anorexia ( Taylor et al, 2022 ). This could potentially explain the absence of effects of BCAA supplementation on mTOR pathway in the intestine and CT, which might in turn account for the limited impact of BCAA supplementation on intestinal health and immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the mTOR pathway is more sensitive to BCAA in the skeletal muscle ( Yoshizawa et al, 2013 ) where the majority of its uptake occurs ( Holeček, 2018 ). Consequently, BCAA supplementation could primarily benefit the skeletal muscle for protein synthesis rather than intestinal epithelial cells and immune cells, especially during Eimeria infection, where nutrient availability is reduced due to anorexia ( Taylor et al, 2022 ). This could potentially explain the absence of effects of BCAA supplementation on mTOR pathway in the intestine and CT, which might in turn account for the limited impact of BCAA supplementation on intestinal health and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-way ANOVA was conducted for all data except for the histology data to examine the main effects (diet and Eimeria challenge) and their interaction. For the histology data, a 2-way ANCOVA was performed with the body weight ( BW ) at sampling as a covariate to account for a priori differences in performance ( Sakkas et al, 2018 ; Taylor et al, 2022 ). When significant differences were observed, Tukey's multiple comparison test was applied to separate and compare the treatment means.…”
Section: Methodsmentioning
confidence: 99%
“…Oikeh et al reported that the ADG/BW (body weight) were decreased in broilers fed a basal grower diet diluted with 0%, 5%, 10% or 15% lignocellulose [ 35 ]. Another study reported that the ADFI was increased with the diets dilution in broilers infected with Eimeria maxima, and the diets were a basal grower diet diluted with 0%, 5%, 10% or 15% lignocellulose [ 36 ]. The inclusion of fiber, such as oat hulls, wood shavings and soybean hulls, has been shown to increase feed efficiency by 3–5% and increase body weight by 2–5% when included at 3–5% in the broiler diets [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth performance response was partitioned into phases relative to the day of inoculation (prepatent, acute, recovery, and compensatory growth): prepatent (d0–3pi), acute (d4–7pi), recovery (d8–14pi), and compensatory phase (29–35d); the periods were defined as per Taylor et al (2022) . The end of prepatent, acute, recovery, and compensatory phases, when birds were weighed, corresponded to 4, 7, 14, and 21 d postinnoculation ( dpi ).…”
Section: Methodsmentioning
confidence: 99%
“…Coccidiosis is a widespread enteric disease caused by protozoan parasites belonging to the Eimeria genus. Eimeria infections lead to reduced availability of dietary amino acids ( AA ) for broiler growth, primarily due to pathogen-induced anorexia and disruptions in amino acid digestion and absorption ( Taylor et al, 2022 ). This, in turn, results in poor growth and elevated mortality rates ( Teng et al, 2020 ; Sharma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%